The effectiveness of emotion therapy training on flexibility and self-control of women in Isfahan - Amirian, Marziyeh; Ghajavandi, Kazem (Psychology of Woman Journal, 2020)
The main goal of this research was to determine the effectiveness of education based on emotion-oriented therapy on the flexibility and self-control of women in Isfahan city. The research method was semi-experimental; The target population in this research was all the women of Isfahan city, 30 of them were selected by the available sampling method; Tangney’s self-control questionnaires (2004) and Asad Beigi’s flexibility questionnaire (2013) were used to collecting information. Also, the experimental group implemented emotion-oriented treatment behavior in eight sessions; the results showed that emotional therapy behavior analysis training affects psychological flexibility. Based on research findings, emotion-oriented therapy training is effective in self-control.